Study on the Modeling of Vehicle Self- excited Shimmy - Tang Wang; Hai Chenguang (Jixie chuandong)
Aiming at the current situation of existing vehicle dynamics model does not have the ability to accurate simulate the dynamic process of vehicle shimmy,a vehicle model is developed for simulation of the dynamics process of vehicle self- excited shimmy. Through the overall dynamics modeling of the steering system,the mechanical correlation between left and right steering wheels is established. Through the steering dry friction model,it is accurately describes the static friction characteristics at the steering kingpin. By using the wheel model,the accurately describes of the elastic characteristics of tire is carried out. Through the simulation of typical operating conditions,the ability to accurate simulate the dynamic process of vehicle self- excited shimmy of the model is verified. The simulation research of the key parameters influence on the self- excited type shimmy is carried out,then some measures to avoid shimmy are given.